2007
DOI: 10.1017/s1047951107000844
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double-blind, placebo controlled trial of beta-blockade in patients who have undergone surgical correction of tetralogy of Fallot

Abstract: Beta blockade with Bisoprolol seems to have no beneficial effect on asymptomatic or mildly symptomatic patients with right ventricular dysfunction secondary to repaired tetralogy of Fallot with residual pulmonary regurgitation and/or stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…(39) BNP and ANP levels increased when compared to patients receiving placebo. This preliminary data discourages systematic use of beta-blockers in this population.…”
Section: A B C D Ementioning
confidence: 86%
“…(39) BNP and ANP levels increased when compared to patients receiving placebo. This preliminary data discourages systematic use of beta-blockers in this population.…”
Section: A B C D Ementioning
confidence: 86%
“…In addition, patients randomized to bisoprolol actually demonstrated an increase in BNP that was not seen in the placebo group. 248 Ramipril in 64 TOF patients with pulmonary regurgitation and RV dilation, in whom the mean baseline RVEF was only mildly reduced (53%), produced no improvement in RV or LV function, exercise capacity, or degree of pulmonary regurgitation. However, RV and LV long-axis shortening significantly improved in the ramipril group, and as mentioned above, ramipril also improved LV volume and EF in patients with restrictive physiology.…”
Section: Medical Therapymentioning
confidence: 93%
“…These results are in accordance with our recently published data, that show no beneficial effects of bisoprolol therapy with regard to clinical and neurohumoral activation. 40 In a multicenter study, Shaddy et al confirmed the lack of positive effect of carvedilol on children with heart defects, probably as a result of the missing benefit on right heart failure. 41 Taken together, we did not observe a reduction of cytokine concentrations in asymptomatic or minimal symptomatic TOF patients treated with bisoprolol.…”
Section: Discusssionmentioning
confidence: 96%